1997
DOI: 10.1107/s010876819601097x
|View full text |Cite
|
Sign up to set email alerts
|

Ag2Ti2P2S11: A New Layered Thiophosphate. Synthesis, Structure Determination and Temperature Dependence of the Silver Distribution

Abstract: uppermost filled levels. In the vanadium case, forThe new Ag2Ti2P2SI1 quaternary phosphosulfide instance, 'V2P2S 6' does not exist, but a mixedvalence phase viii vlI f]0.22PS3 is found instead --0.44--0.34 t disilver dititanium undecathiodiphosphate is obtained (Ouvrard, FrSour, Brec & Rouxel, 1985). The by heating the elements at ca 850K in an vanadium higher oxidation state V Ill can be isolated , 1985), which present different compound can be written as Ag2Tl z Pz ($2) S 9 . A structural patterns. To stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…The mean Ti}S and P}S distances indicate that the cations are in the Ti'4 and P4 states, according to their ionic radii (21). Some of the Ag atoms in both of the structures exhibit high displacement parameters in agreement with (i) the d electronic con"guration of the Ag> cations (22) and (ii) their weak localization in the tunnels of the structural frameworks.…”
Section: Structures Descriptionmentioning
confidence: 63%
“…The mean Ti}S and P}S distances indicate that the cations are in the Ti'4 and P4 states, according to their ionic radii (21). Some of the Ag atoms in both of the structures exhibit high displacement parameters in agreement with (i) the d electronic con"guration of the Ag> cations (22) and (ii) their weak localization in the tunnels of the structural frameworks.…”
Section: Structures Descriptionmentioning
confidence: 63%
“…Gaudin et al (1997) and van der Lee et al (1993) studied the synthetic compounds Ag 2 Ti 2 P 2 S 11 and Ag 2 MnP 2 S 6 by single-crystal X-ray diffraction and showed that the Ag atoms are observed to move from a lower coordination (triangular) to a higher coordination (tetrahedral) upon increasing the temperature. Surprisingly, in samsonite structure we observed the opposite situation with a smearing of the electron density toward the lower coordination sites with increasing the temperature.…”
Section: Description Of the Structurementioning
confidence: 96%
“…The case of samsonite, Ag 4 MnSb 2 S 6 LUCA BINDI 1, * AND MICHEL EVAIN 2 of nonconducting materials (van der Lee et al 1993;Boucher et al 1994;Gaudin et al 1997) and of fast ion conducting phases (Kuhs and Heger 1979;Boucher et al 1992Boucher et al , 1993Evain et al 1998). Recently it has been used in solving complex structures in the pearceite-polybasite mineral family Bindi et al 2006aBindi et al , 2006bBindi et al , 2006c.…”
Section: Gram-charlier Development Of the Atomic Displacement Factorsmentioning
confidence: 97%
“…Such an approach is used to refine already known structures with suspiciously high R values and/ or high isotropic displacement parameters for Ag or Cu atoms. The non-harmonic approach has been used successfully over the past twenty years to solve numerous structures of non-conducting materials (van der Lee et al, 1993;Boucher et al, 1994;Gaudin et al, 1997) and ion-conducting phases (Kuhs and Heger, 1979;Boucher et al, 1992Boucher et al, , 1993Haile et al, 1997;Evain et al, 1998;Haile and Wuensch, 2000a,b,c). Recently, it has been used to solve complex structures of natural and synthetic sulphosalts and the pearceitepolybasite mineral family: (Evain et al, 2006a,b;Bindi et al, 2006aBindi et al, ,b, 2007; fettelite, (Bindi et al, 2009); synthetic skinnerite, (Pfitzner, 1998); synthetic tetrahedrite, (Pfitzner et al, 1997).…”
Section: Introductionmentioning
confidence: 99%